A socio-religious hybridity strategy to respond to the problems of religious studies in Zimbabwe - Dube, Bekithemba (University of the Free State, 2016)
The aim of the study was to design a socio-religious hybridity strategy that attempts to respond to the problems of Religious Studies in Zimbabwean secondary schools. The strategy emerged against the background of several challenges with the current multifaith approach to Religious Studies, which excludes other local religions from the curriculum. The curriculum is largely Christocentric, implying that the Christian religion is extensively covered. The aims of the syllabus seem to indicate that there is a need to teach various religions, but the content of the syllabus does not give space to other religions. This creates a monothelic curriculum that ignores the fact that some of the children have a religious orientation that may not necessarily be Christian. Secondly, the Religious Studies curriculum is not socially responsive to arm learners with knowledge on how to avert religious abuse, which is becoming rampant in Zimbabwean society. Religious Studies is failing to respond to religious abuse. The other challenge is that the indigenous knowledge system is not adequately covered, although it is important for the survival of the local people. The syllabus is silent on the indigenous knowledge system. However, the national examination system gives learners questions relating to indigenous knowledge, with a low mark allocation compared to the mark for Biblical question. This gives learners and teachers the perception that indigenous knowledge is unimportant for their survival. The other significant challenge is that the majority of the Religious Studies teachers in Matabeleland North are not trained to teach the subject, neither are they adequately prepared to teach other religions apart from the Christian faith. In response to these and other problems, this research study proposes a socioreligious hybridity strategy that will ensure a relevant curriculum that addresses the religious needs of all learners through a hybridity approach. The strategy seeks to ensure that Religious Studies is in line with democratic practices such as social justice, equity, recognition, inclusivity and improvement of human conditions. It will go a long way to contributing towards the peaceful co-existence of various religious groups and consequently improving the lives of people through the study of religion. The study is grounded on critical emancipatory research, a theoretical framework that dates back to the Frankfurt School of 1923. It has five working principles: the improvement of the human condition, elimination of false consciousness, social transformation, social justice and emancipation. These principles underpinned the study and they become lenses through which to interrogate Religious Studies in Zimbabwean schools. To complement the framework, I used participatory action research to generate data with the coresearchers. Participatory action research was chosen for its emancipatory tendencies and because it seeks to work with disadvantaged members of the community. The approach values its coresearchers as equal partners and believes that the people with the problems are the ones with sustainable solutions. In the study, I worked with a hybridity team consisting of representatives of various religious groups, such as Christianity, Islam, Judaism, African religion, together with local leaders, Religious Studies teachers and learners in Matabeleland North. The hybridity team’s shared vision was to develop a strategy that responds to the challenges of Religious Studies in Zimbabwean schools. The team participated in discussions, workshops, and class observations and the focus was to generate data that responded to the objectives of the study. The generated data was subjected to critical discourse analysis, chosen because of its focus on power relations, which are often problematic in the religious environment. Critical discourse analysis complements critical emancipatory research and participatory action research in the fight for the marginalised members of the community. Data was analysed through three lenses, namely the textual, discursive and social practice level. The findings of the research were used to formulate a socio-religious hybridity strategy. I have found that the hybridity of religions is a desirable way to improve the teaching and learning of Religious Studies. Owing to their lack of comprehensive religious knowledge and prejudice, people tend to be afraid to engage other religions. It further emerged that recognising other religions as valid goes a long way to promote a culture of peace in society, reducing the tendency of people using violence to express their feelings. The study revealed that religious extremists are often the perpetrators of human abuse. Hence, people need to moderate their beliefs to achieve social justice and recognise the good in other religions.Based on the generated data, I formulated a strategy that responds to the challenges of Religious Studies to foster curriculum relevance for the learners. The limitation of the strategy is that it does not address ways in which extremists can be engaged to moderate their religious views, especially those that violate human rights, such as terrorism. My hope is that other researchers will explore this weakness to improve Religious Studies in Zimbabwean schools. I recommend the use of this strategy in the quest for curriculum relevance in Zimbabwean schools and elsewhere.

Die doel van die studie was om ‘n sosio-religieuse hibridiese strategie te ontwerp wat reageer op die problem van Godsdiensstudies in Zimbabwiese sekondêre skole. Die strategie het teen die agtergrond van verskeie uitdagings binne die huidige veelsydige geloofs benaderings van Godsdiensstudies ten vore gekom. Die benaderings sluit ander gelowe uit van die kurrikulum. Die kurrikulum is hoofsaaklik Christosentries wat impliseër dat dit hoofsaaklik net die Christengeloof dek. Die doel van die leerplan dui daarop aan dat daar ‘n nodigheid bestaan vir die leer van verskeie Godsdienste maar die inhoud van die leerplan laat nie ruimte daaraan toe nie. Dit veroorsaak ‘n monolitiese kurrikulum wat die feit ignorer dat van die kinders se godsdienste oriëntasie nie noodsaaklik Christenskap is nie. Tweedens, is die Godsdiensstudie kurrikulum nie sosiaal vatbaar om leerders met die kennis toe te rus om godsdienstige mishandeling af te weer nie wat hoogty vier in die Zimbabwiese samelewing. Die ander uitdaging is dat die inheemse kennisbasis nie voldoende aangespreek word nie alhoewel dit ‘n belangrike rol speel in die oorlewing van die plaaslike boorlinge. Die leerplan spreuk glad nie die inheemse kennisbasis aan nie. Alhoewel die nasionale eksamen sisteem hom daartoe leen om leerders vrae oor die inheemse kennisbasis te vra word ‘n lae punt toegeken aan die antwoorde in vergelyking met Bybelse vrae. Dit veroorsaak ‘n persepsie onder die onderwysers en leerders dat inheemse kennis van geen belang vir oorlewing is nie. Die ander betekenisvolle uitdaging is dat die meerderheid van die Godsdiensstudie onderwysers in Matabeleland-Noord nie opgelei is om die vak aan te bied nie en dus ook nie bereid is om ander godsdienste as die Christendom aan te bied nie. In antwoord op hierdie en ander probIeme, stel hierdie studie voor dat ‘n sosioreligieuse hibridiese strategie sal toesien dat ‘n relevante kurrikulum ontwerp sal word wat die godsdienstige tekortkominge van alle leerders sal aanspreek deur ‘n hibridiese benadering. Die strategie mik daarop om toe te sien dat Godsdiensstudies in lyn is met demokratiese praktyke soos sosiale geregtigheid, gelykheid, erkenning, omvattende en verbeterde menslike toestande. Dit sal bydra tot die vreedsame bestaan van verskeie godsdienstige groepe en die lewe van die mense deur religieuse studie verbeter. Die studie is gegrond op kritiese vrywaringsnavorsing wat ‘n teoretiese raamwerk is wat terug dateer na die Frankfurt Skool in 1923. Dit bestaan uit vyf werkende beginsels, naamlik: die verbetering van menslike omstandighede, eliminasie van false bewustheid, sosiale transformasie en emansipasie. Hierdie beginsels onderstreep die studie en hulle word dan lense waardeur die Godsdiensstudies in Zimbabwiese skole ondervra kan word. Om die raamwerk aan te vul, het ek gebruik gemaak van deelnemende aksienavorsing om data te genereer tesame met die mede navorsers. Deelnemende aksienavorsing is gekies vir die vrywarende tendense wat dit lewer an omrede dit saamwerk met benadeelde lede van die gemeenskap. Hierdie benadering erken die rol van die mede navorsers as gelyke vennote en glo dat die mense met die problem ook die mense is met volhoubare oplossings. In hierdie studie het saam gewerk met ‘n hibridiese span wat bestaan uit verskeie godsdienstige groepe soos Christene, Islam, Judaïsme, Afrika godsdiens tesame met plaaslike leiers, Religieuse opvoeder en leerders van Matabeleland-Noord. Die hibridiese span se gedeelde visioen was om ‘n strategie te ontwerp wat antwoord op die uitdagings van Religieuse Studies in Zimbabwiese skole. Die span het deelgeneem aan besprekings, werkswinkels en klasobservasies en die fokus was om data te genereer wat antwoord op die mikpunte van die studie. Die genereerde data is blootgelê aan kritiese diskoersanalise wat gekies is omrede dit focus op kragverhoudings wat gereeld problematies is in die godsdienste omgewing. Kritiese diskoersanalise komplimenteer kritiese vrywaringsnavorsing en deelnemende aksienavorsing in die strewe vir marganiliseërde lede van die gemeenskap. Die data is deur drie lense geanaliseër, naamlik tekstueel, breedvoerig en sosiale praktyk. Die bevindinge van die navorsing is gebruik om ‘n sosio-religieuse hibridiese strategie te formuleer. Ek het ondervind dat die hubriditeit van godsdienste ‘n begeerlike wyse is om die opvoeding en leer van Godsdiensstudies te verbeter. Weens die gebrek aan uitgebreide godsdienstige kennis en bevooroordeeldheid, neig mense om bang te wees om ander godsdienste te betrek. Dit het vêrder gebleik dat as ander godsdienste erken word, dit ‘n kultuur van vrede in die samelewing te weeg sou bring wat die tendens van geweld as ‘n uitdrukking van emosies sou verminder. Die studie het onthul dat godsdienstige ekstremiste gewoonlik die persone is wat menslike mishandeling pleeg. Dus is dit nodig vir mense om hulle geloofsoortuigings te wysig om sosiale geregtigheid te bereik en die goeie aspek van ander godsdiensgroepe te herken. Om die kurrikulum relevansie vir leerders te koester, het ek die strategie geformuleer op die genereerde data wat antwoord op die uitdagings wat Godsdiensstudies bied. Die limitasie van die studie is nie dat dit maniere aanspreek van hoe die ekstremiste betrek kan word om hulle geloofsoortuigings te wysig nie, veral met die skending van menseregte deur middel van terrorisme. My hoop is dat ander navorsers hierdie swakheid sal ondersoek om Godsdiensstudies in Zimbabwiese skole te verbeter. I beveel die gebruik van hierdie strategie aan in die strewe na kurrikulum relevansie in Zimbabwiese skole en elders.
Dissertation (Ph.D. (Curriculum Studies))--University of the Free State, 2016
Keywords: Hybridity; Curriculum relevance; Critical emancipatory research; Critical discourse analysis; Participatory action research; Teacher capacitation; Religious inclusivism; Indigenous knowledge systems; Religious studies; Religion -- Study and teaching -- Zimbabwe